Hexane Fraction of Turbo brunneus Inhibits Intermediates of RANK-RANKL Signaling Pathway and Prevent Ovariectomy Induced Bone Loss - Chaugule, Sachin; Kashipathi Sureshbabu, Shalini; Dakave, Suresh; Krishna, C. Murali; Chaudhari, Pradip; Indap, Madhavi; Chiplunkar, Shubhada (Frontiers in Endocrinology, 2019)
Osteoporosis is a “silent disease” characterized by fragile and impaired bone quality. Bone fracture results in increased mortality and poor quality of life in aged people particularly in postmenopausal women. Bone is maintained through the delicate balance between osteoclast-mediated bone resorption and osteoblast-mediated bone formation. The imbalance is caused most often by overly active osteoclasts due to estrogen deficiency. Natural products have long been used to prevent and treat osteoporosis since they have fewer side effects. The marine environment is a potential source of biologically and structurally novel biomolecules with promising biological activities but is less explored for the treatment of bone-related diseases. The present study aims to evaluate the antiosteoporotic effect of Hexane fraction of Turbo brunneus methanolic extract (HxTME) and to investigate its role in RANK-RANKL signaling pathway using in vitro osteoclasts cultures and in vivo ovariectomized (OVX) Swiss mice model. The present study demonstrated that the HxTME significantly inhibited RANKL induced osteoclast differentiation and maturation in vitro. HxTME completely downregulated the mRNA expression of key transcription factors such as NFATc1, c-FOS, and osteoclasts related genes involved in osteoclastogenesis. In vivo studies also depicted the effectiveness of HxTME in ovariectomized mice by preserving bone microarchitecture, mineral content, and inhibiting bone loss in treated mice as analyzed by Histomorphometry, MicroCT, and Raman spectroscopy. Oral administration of HxTME fraction resulted in the decreased percentage of F4/80+, CD11b+, and CD4+ RANKL+ T cells in OVX mice whereas pro-osteoclastic cytokine, IL6 was markedly reduced upon treatment with HxTME. On stimulation with PMA/Io and PHA, a significant decrease in proliferative response in the splenocytes of HxTME treated OVX mice was observed. Fatty acid profiling revealed that HxTME is rich in ω3 and ω6 polyunsaturated fatty acids (PUFAs), which have high nutraceutical properties and are known to play important role in growth, development and maintenance of health. Therefore, HxTME may be a good source of nutraceutical in the treatment of bone-related diseases particularly in postmenopausal osteoporosis and may be pursued as a potential candidate for treatment and management of osteoporosis.